The Effect of Irradiation of Fe and Ar Ion on the Surface Morphology of Diamond Thin Film Related to the Magnetoresistance Property - Mustofa, Salim; Purwanto, Setyo; Mishima, Kenji (Makara Journal of Technology, 2016)
The irradiation of Fe and Ar ion was applied on the surface of diamond/Si thin film to know its effect on the morphology of thin film.The magnetoresistance property was also studied. Ion irradiation treatment using Fe ion followed by argon ion at the energy of 70keV and a dose of 1 x 1015 ion/cm2 have been conducted on the surface of two types of thin film, diamond/Si (111) and diamond/Si (100). Both thin films were made by using a CVD method, and the thickness of the thin film is 1000-nm. From simulations using the software called Stopping and Range of Ions in Matter (SRIM), it is known that Fe and Argon ion penetration into the surface of the thin film are respectively 512 and 603 Angstroms. After that the thin film sample was irradiated with ion Fe and Ar, and the property behavior of the morphological change of thin film were studied through Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). The grain size range of thin film on diamond films / Si (100) was reduced from 115-322 nm to 147-169 nm, suggesting the effect of irradiation on the surface morphology. The magnetoresistance property is approximately 0.15% at room temperature and magnetic field external H = 0.8 Tesla.